Systemic lupus erythematosus and epilepsy: A Mendelian randomization study - Yang Hu; Duo Lin; Dongmei Wu; Yuqing Zhang; Gongbo Li (Epilepsia Open)
Abstract Objective Numerous observational studies have found a relationship between systemic lupus erythematosus (SLE) and epilepsy; however, their causal relationship remains unclear. This study aimed to investigate the causal role of SLE in epilepsy or any of its subtypes using a two‐sample Mendelian randomization (MR) analysis. Methods Single nucleotide polymorphisms (SNPs) linked to SLE were utilized as instrumental variables in MR analysis to assess their causal impact on epilepsy. The primary MR findings were derived using the inverse variance weighted (IVW) method, which was further supported by the weighted median and MR‐Egger regression techniques. Additionally, sensitivity analyses, including Cochran's Q test and pleiotropy tests, were conducted to evaluate the influence of these SNPs on epilepsy, particularly looking for signs of horizontal pleiotropy and heterogeneity. Results We selected 43 SNPs that reached genome‐wide significance from genome‐wide association studies (GWASs) on SLE to serve as instrumental variables in this study. The IVW method showed no evidence to support a causal association between SLE and epilepsy (all epilepsy: odds ratio (OR) = 1.006, 95% confidence interval (CI) = 0.994–1.018; focal epilepsy: OR = 1.006, 95% CI = 0.994–1.019; generalized epilepsy: OR = 1.015, 95% CI = 0.996–1.035). Other MR complementary methods revealed consistent results. Furthermore, there was no evidence indicating heterogeneity or horizontal pleiotropy. Significance The findings of MR analysis did not support a genetically predicted causal relationship between SLE and epilepsy, but emphasized the need for further research on shared pathophysiological mechanisms, particularly the role of immune system abnormalities and potential influences such as chronic inflammation and therapeutic interventions. Plain Language Summary The etiology of epilepsy is complex and diverse, including immune factors. Through a Mendelian randomization analysis, we did not find evidence of a genetic causal relationship between systemic lupus erythematosus and epilepsy. However, this does not invalidate epidemiological evidence, and further exploration is needed to investigate factors influencing the relationship between the two.